Capital unchained: finance, intangible assets and the double life of capital in the offshore world. Issue 1 (2nd January 2017) - Bryan, Dick; Rafferty, Michael; Wigan, Duncan
ABSTRACT: The rise of intangible assets such as brand names, research and development, patents and other forms of abstract capital such as digital platforms and data flows has confounded extant measures and concepts of capital and accumulation. What used to be a residual asset category known as 'goodwill' has now overtaken so-called fixed or tangible assets in the profitability and valuation of many leading corporations. Yet these intangible assets lead a double life as both spatial and temporal in some dimensions, yet fluid and spatio-temporally elusive in others. Using a framework focused on measuring (by accountants), managing (by corporations) and monitoring (by International Political Economy scholars and regulators), this article explores the longer term implications of accumulation of internationalised capital in intangible and abstract forms, and the prominent role of finance and offshore in giving mobility and fluidity to these forms of capital. The article suggests that while global value chain and global production network analyses have helped researchers and policy-makers to track increasingly fragmented and fluid networks of commodity production, there also is a need to follow the global double life of internationalised and financialised intangible assets and wealth flows, and parallel reorganisations of state forms in response to those transformations.